PEMANFAATAN SMART TV UNTUK MENGOPTIMALKAN KETERAMPILAN MENYIMAK PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS 3 DI SD RIYADUL ARKHAM - Azizah, Nurul; Ariefian, Novalia; Febriyanti, Fina; Karomah, Nawwirul; Amelia, Ica Jehian; Suwandayani, Beti Istanti (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to describe the use of Smart TVs in improving listening skills among third-grade students at Riyadul Arkham Elementary School. The background of this study stems from the low level of attention and concentration among students when participating in listening activities and the suboptimal use of Smart TVs in the classroom. The method used in this study is a qualitative approach with a descriptive method involving observation, semi-structured interviews, and documentation. The data analysis process used the Miles and Huberman model, which includes the steps of data reduction, data presentation, and conclusion drawing. The findings from the study indicate that the use of Smart TV can effectively increase students' attention, motivation, and involvement in the listening learning process with audiovisual displays that are clearer, more interesting, and easier to understand. The visual elements, sounds, and animations displayed help students stay focused and better understand the verbal information. In addition, the success of the learning process is also influenced by the way teachers introduce the material and conduct question and answer sessions after the video is played. The suitability of audiovisual material to the cognitive development stage of students is also a major factor that supports the effectiveness of learning. Overall, the use of Smart TV has the potential to improve the quality of listening learning at the elementary school level. The results of this study recommend that training be provided for teachers and that appropriate audiovisual material be selected to maximize its implementation.